Comprehensive Adsorption Studies of Doxycycline and Ciprofloxacin Antibiotics by Biochars Prepared at Different Temperatures - Zhi-wei Zeng (Frontiers in Chemistry, 2018)
This paper comparatively investigated the removal efficiency and mechanisms of rice straw biochars prepared under three pyrolytic temperatures for two kinds of tetracycline and quinolone antibiotics (doxycycline and ciprofloxacin). The influencing factors of antibiotic adsorption (including biochar dosage, pH, background electrolytes, humic acid, initial antibiotics concentration, contact time, and temperature) were comprehensively studied. The results suggest that biochars produced at high-temperature [i.e., 700°C (BC700)], have higher adsorption capacity for the two antibiotics than low-temperature (i.e., 300–500°C) biochars (BC300 and BC500). Higher surface area gives rise to greater volume of micropores and mesopores, and higher graphitic surfaces of the BC700 contributed to its higher functionality. The maximum adsorption capacity was found to be in the following order: DOX > CIP. The π-π EDA interaction and hydrogen bonding might be the predominant adsorption mechanisms. Findings in this study highlight the important roles of high-temperature biochars in controlling the contamination of tetracycline and quinolone antibiotics in the environment.